Caracterização e triagem ligninolítica de fungos filamentosos isolados de aves migratórias provenientes da Fundação Parque Zoológico de São Paulo - Santos, Meryellen Pereira [UNIFESP] (2014)
Fungi are the great decomposers of organic matter and many of them are able to degrade complex organic matter like celulose, hemicelulose and lignina. These compounds can be used as microbial sources for carbon and therefore reintroduced in biogeochemical cycles. Fungi are being reported as specialized in degradation different substrates and they are becoming more competitive than bactéria. Nowadays, they are having great relevance in studies related to biodegradation of polycyclic aromatic hydrocarbons (PAHs), through the action of non-specific extracelular enzymes: lignin peroxidase(LiP), manganese peroxidase (MnP) and laccase(Lac). In this contexto, the aim of this study was to evaluate strains of filamentous fungi isolated from sapling of choana and cloaca of migratory birds that were living at São Paulo Zoo Park Foundation during May to September, 2012. It was isolated 58 fungal strains. These isolates were sreened about their ligninolytic ability though the guaiacol oxidation in BKG agar. Twenty three(23) strains were selected and morphologically characterized as Fusarium spp. Though qualitative and quantitative spectrophometric analyses, it was possible to select promise strains about lignin peroxidase(LiP), manganese peroxidase (MnP) and laccase(Lac) activites. The ligninolytic activity, under polyaromatic compounds considered as environmental contaminants from textile industries, like RBBR(Remazol Brilliant Blue R), was investigated as well. Five strains were selected. AM03, AM06, AM10, AM28 and AM35. These isolates were also investigated through chromatographic analyses, evaluating their potential to biodegrade naphthalene or pyrene as sole carbono sources in minimum mineral médium. One strain (AM28) was selected and allowed us to pretict that it could be promisors for future applications in environmental bioremediation of polluted área rich in polycyclic aromatic compounds such as textile dyes manufacturer, paper industry and petroleum exploration.